Persuasive Proposals and Presentations: 24 Lessons for Writing Winners - Pierce Heather (American : McGraw -Hill, 2004)
Contents
Persuasive Proposals and Presentations shows readers how to develop a winning strategy and how to be clear, organized, and persuasive. It lays out common mistakes in strategy and offers effective advice.
Tell readers what they want to hear * Focus on a theme * Detail unique qualifications * Stick to the point * Use endorsements effectively * Write for your audience * Create organized appendices * Enhance readability.
Keywords: Persuasive Proposals and Presentations